SECTORAL ANALYSIS OF BANKS ON TRENDS OF OPENING ACCOUNTS FOR PRADHAN MANTRI JAN DHAN YOJNA PHASE I (PMJDY) - Shukla, Trilok Nath (International Journal of Research -GRANTHAALAYAH, 2017)
Most recently a national mission on financial inclusion called “PRADHAN MANTRI JAN - DHAN YOJANA” was launched on the 28th of August 2014. Under the direct supervision of the Indian Prime Minister and the Department of Financial Services, Ministry of Finance, the objective of this mission is to enroll over 70 million households and open their bank accounts along with providing them as a first step a RuPay debit card with a Rs. 1,00,000/- accident cover. In the due course of time the plan is to also cover these account holders with insurance and pension products. About 60% of the population in India does not have access to a bank account. PMJDY aims at providing bank account to single household above the age of 10 years who do not have bank account and will be opened with zero balance. The household opening the account will be benefited with one lakh accidental cover and Thirty Thousand life cover without premium. People opening account under this scheme will also avail overdraft facility up to five thousand from the bank after satisfactory conduct of the account for 6 months.